Pengaruh Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Pasar Malam Di Desa Kasiro Kecamatan Batang Asai Kabupaten Sarolangun - Khusnul Istiqomah; M. Nazori; Ahmad Dono (Journal of Islamic Economics and Finance, 2023)
The phenomenon that occurs at the Kasiro Village Night Market is that the average traders at the Kasiro Village Night Market have not provided good service, and most people prefer shopping at the night market rather than shopping at street vendors. The purpose of this study was to determine the effect of price and service quality on consumers at the village of Kasiro night market. The method used in this research is quantitative research, data collection is used by observation, interviews, documentation and questionnaires. In this study using a sample of 96 people. The data analysts used in this study are validity test, reliability test, classical assumption test, descriptive statistical test, and multiple linear regression test, namely the coefficient of determination test, T test and F test.Based on research data processing, the results obtained for the price variable (X1) partially with a significance level less than 0.05, namely with a significance level of 0.000 <0.05, it can be said that the price variable has a significant effect on purchasing decisions. Whereas for the service quality variable (X2) partially with a significance level greater than 0.05, namely with a significance level of 0.678> 0.05, it can be said that the price variable has no effect on purchasing decisions. Furthermore, by using the F test to obtain a significance value that is 0.001 less than 0.05, the regression model can be used to predict that price and service quality together influence purchasing decisions.